Evaluación productiva y análisis microeconómico del maní forrajero perenne (Arachis pintoi) en un sistema de levante-ceba de porcinos en confinamiento (2006)
ABSTRACT: To make an evaluation of the productive and micro-economic aspects of Arachis pintoi as a partial replacement of crude protein in pigs a group of 12 female pigs & was studied under four randomly asigned subgroups: T1: Witness group, was fed commercial concentrate; in subgroups T2, T3 and T4, 10, 20 and 30%, respectively, of their dietary protein was replaced by Arachis pintoi. The evaluated variables were intake, corporal weight, daily gain of weight, back fat, nutritional conversion and the relation between the feed cost and the value of the weight gained. The results indicate that there were no significant statistical differences between the different treatments for any of the evaluated variables, except for the average daily weight gained during the raising stage (p <0.01), with the greater values for T1 (1.01 kg/animal/day) and the lowest for T4 (0.78 kg/animal/day). The microeconomic analysis shows that the smaller cost associated to the production of 1 kg of pig was obtained for T3, 45% with respect to T1. The behavior of the gross partial gain was superior for T3, 46% higher than T1. This was therefore the treatment presenting the better conversion.